Therapeutic Implications of PPARγ in Cardiovascular Diseases - Hiroshi Hasegawa; Hiroyuki Takano; Issei Komuro (PPAR Research)
Peroxisome proliferator-activated receptor-γ (PPARγ) is the members of the nuclear receptor superfamily as a master transcriptional factor that promotes differentiation of preadipocytes by activating adipose-specific gene expression. Although PPARγ is expressed predominantly in adipose tissue and associated with adipocyte differentiation and glucose homeostasis, PPARγ is also present in a variety of cell types including vascular cells and cardiomyocytes. Activation of PPARγ suppresses production of inflammatory cytokines, and there is accumulating data that PPARγ ligands exert antihypertrophy of cardiomyocytes and anti-inflammatory, antioxidative, and antiproliferative effects on vascular wall cells and cardiomyocytes. In addition, activation of PPARγ is implicated in the regulation of endothelial function, proliferation and migration of vascular smooth muscle cells, and activation of macrophages. Many studies suggest that PPARγ ligands not only ameliorate insulin sensitivity, but also have pleiotropic effects on the pathophysiology of atherosclerosis, cardiac hypertrophy, ischemic heart, and myocarditis.